Novas tecnologias e ensino de Língua Portuguesa: a pedagogia do digital na educação linguística - Pereira, Cátia Luciana (2015)
The present thesis has as objective the investigation of the link between Portuguese Language and new technologies in classroom theory and practical exercises, due to the concern regarding Portuguese Language teaching in High School and its relation to technology and to the necessity to provide theoretical and methodological aid to support pedagogic practices that integrate these fields. For such, we surveyed official documents in this area, we sought to understand scientific knowledge related to both fields, we have analyzed a textbook chapter, we have verified if, in this chapter, such relations become effective considering the treatment given to the blog, and we propose a didactic sequence to complement the textbook approach. The student s communicative competence is a necessary condition to citizenship practice, as it allows the individuals to become critical readers that will know how to express themselves in both oral and written modalities of the language, adapting to the most diverse communicative situations. As the objective of Portuguese Language discipline at school today is to enable such communicative competence, it is nonsensical to keep separated, as it is traditionally done, the exercises of reading, interpreting, producing texts and analyzing grammar, as well as the exercises of digital technologies. This reality, which should connect the school role, the Portuguese Language teaching and technologies, leads us to formulate two research questions: 1 - What are the assumptions needed to conceive new technologies as Digital Pedagogy components? 2 - How does a High School textbook propose the articulation of the six Pedagogies of Linguistic Education? The Linguistic Education is the theoretical foundation of this study, especially when it comes to the integration of pedagogies of orality, writing, reading, lexicon-grammar and literature to which we add what we have denominated as digital pedagogy. This is proposed because digital competence is today one of the composing elements of communicative competence to be passed onto our students and, as we see it, just as important as the other types of competence